2021
DOI: 10.3390/curroncol28050355
|View full text |Cite
|
Sign up to set email alerts
|

At the Heart of It All: Emotions of Consequence for the Conceptualization of Caregiver-Reported Outcomes in the Context of Colorectal Cancer

Abstract: Colorectal cancer (CRC) can be demanding for primary caregivers; yet, there is insufficient evidence describing the caregiver-reported outcomes (CROs) that matter most to caregivers. CROs refer to caregivers’ assessments of their own health status as a result of supporting a patient. The study purpose was to describe the emotions that were most impactful to caregivers of patients with CRC, and how the importance caregivers attribute to these emotions changed from diagnosis throughout treatment. Guided by quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Humanity care is the core spirit of the nursing discipline, and empathy is necessary for nursing personnel to perform nursing interventions. Narrative nursing refers to the way in which nursing personnel view the problem through the patients' perspective and discover the key points of individual care to propose targeted care options for the patients that realistically address their distress and problems [ 20 , 21 ]. Patients with malignant tumors usually need to receive long-term chemotherapy and are overwhelmed by the body suffering caused by the disease, the toxic side effects from chemotherapy, and the time and money spent on treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Humanity care is the core spirit of the nursing discipline, and empathy is necessary for nursing personnel to perform nursing interventions. Narrative nursing refers to the way in which nursing personnel view the problem through the patients' perspective and discover the key points of individual care to propose targeted care options for the patients that realistically address their distress and problems [ 20 , 21 ]. Patients with malignant tumors usually need to receive long-term chemotherapy and are overwhelmed by the body suffering caused by the disease, the toxic side effects from chemotherapy, and the time and money spent on treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol was approved by the harmonized BC Cancer and University of British Columbia Research Ethics Board. Further details of study methods have been published elsewhere [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…What would you like healthcare providers to do with this information? What type and when would support be helpful/unhelpful to you [ 31 ]? We asked patients similar questions in terms of what they perceived to be caregivers’ experiences and needs.…”
Section: Methodsmentioning
confidence: 99%
“…The limited literature on this topic has shown that patients with head and neck cancer felt that their care was a considerable burden and that it was very hard for their caregiver [13]. To date, few studies have focused on caregivers of patients with digestive cancers but Mosher showed that caregivers and colorectal cancer patients failed to identify the same challenges that caregivers face [14][15][16].…”
Section: Introductionmentioning
confidence: 99%